Structural Optimization of Composite Stiffened Panel of a Transport Aircraft Wing using CAE Tools. (2015) - Kumar, K.C. Nithin; Gupta, Gopal; Lakhera, Saurabh; Shaikh, Amir
Abstract: Structural design optimization of stiffened panels of a typical transport aircraft composite wing is carried out for minimum weight, meeting all the structural design constraints. The design variables are: skin thickness and stringer cross section for different sets of stringer spacings. The Yamuda-Sun Failure Criterion (YSFC) for strength and Panel buckling Factor (PBF) criteria for buckling of panels are incorporated in the optimization. The final configuration of stiffened plate gives the optimum stringer spacing, which gives the minimum weight of stiffened plate for satisfying the strength and buckling constraints. In this study it is found that 125 mm spacing is optimum as compared to 100 mm stringer spacing and with this about 20% weight can be saved.